An Unusual Appearance of Double Right Coronary Artery - Akcay, Ahmet (SAGE-Hindawi Access to Research, 2010)
Double right coronary artery (RCA) is an extremely rare coronary artery anomaly. We aimed to report an atherosclerotic double RCA which appeared after primary percutaneous intervention performed to treat acute inferior myocardial infarction. This is the first case in the literature, which the coronary arteries that can be accepted as double RCA have been hidden by total atherosclerotic occlusion of the proximal part of the RCA. In this paper, also the definition, correct diagnosis, and appropriate diagnostic methods for double RCA were discussed.